Selection of reference genes to quantify relative expression of ochratoxin A-related genes by Penicillium nordicum in dry-cured ham. (December 2017) - Bernáldez, Victoria; Córdoba, Juan J.; Andrade, María J.; Alía, Alberto; Rodríguez, Alicia
Abstract: Penicillium nordicum is an important and consistent producer of ochratoxin A (OTA) in NaCl-rich foods such as dry-cured ham. OTA is a toxic secondary metabolite which provokes negative effects on consumer health. Once OTA is produced in ham, this mycotoxin is difficult to remove. Since gene expression always precedes OTA production, analysis of expression of OTA-related genes by reverse transcription real-time PCR (RT-qPCR) could be a valuable tool to predict OTA contamination in ham. However scarce RT-qPCR protocols are properly validated leading to inconsistent data analyses. The objective of this study was to examine reference genes suitable for normalisation in designing and developing new RT-qPCR methods for quantifying the relative expression of genes involved in OTA biosynthesis ( otapks and otanps ) by P. nordicum on a dry-cured ham model system after 7 days of incubation. Firstly, primers based on three housekeeping genes commonly found in moulds, β-tubulin, COI and ITS, and on the otapks gene were designed. The primer pair F/R-npstr previously developed on the otanps gene was also used. Although most of the designed primers met the requirements needed to be used in qPCR assays, the primer pairs β-tubF1/R1, COI-F1/R1, ITSF2/R2 and otapksF3/R3 for the β-tubulin, COI, ITS and otapks genes, respectively, were selected due to their lowest Cq value. Next, the two assumptions of the 2 −ΔΔC T method to evaluate the relative expression of the otapks and otanps genes were fulfilled for two of the three endogenous genes tested, β-tubulin and COI . However, β-tubulin was considered more proper as reference gene than COI under the environmental conditions assayed since its expression values by day 7 were more related to OTA production. Therefore, the two RT-qPCR methods for the analysis of the relative expression of the otapks and otanps genes have been properly validated and can be used as control tools to avoid or minimise the presence of OTA in ham. Highlights: New validated RT-qPCR to quantify expression of OTA-related genes have been developed. Primers based on β-tubulin, COI and ITS genes were used as endogenous controls. Primers designed upon otapks and otanps genes were utilised as target ones. β-tubulin and COI genes met requisites of the 2 −ΔΔC T method to be reference genes. OTA-related gene based data normalised with β-tubulin is related to OTA levels in ham.